(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2017)
Conodonts are an extinct group of marine animals possessing debated affinities. The conodont elements are composed of calcium phosphate [apatite (CaF)] and collagen-like proteins. Distribution of Sr in the bioapatite of albid, lamellar and paralamellar tissues of some Upper Devonian conodont element crowns from NW Russia was studied by microprobe. The calcium phosphate of the lamellar and paralamellar tissues demonstrates periodical oscillation of Sr contents across the lamellae (0.4-0.5 wt% in the outer part of lamella, and 0.2 wt% in the inner part). The albid tissue contains Sr of less than 0.4 wt%. It is suggested that oscillations of Sr concentrations reflect the periodic growth of the lamellae, and the average Ca/Sr ratio can be a proxy of the growth rate.